Hubungan Hiperglikemia Dengan Kejadian Stroke Hemoragik Pada Pemeriksaan Multislice CT-Scan Kepala Tanpa Kontras Di RSUD DR. Moewardi Surakarta - Fernando Feliz Christyan; . Widiastuti; Jarot Subandono (Nexus Kedokteran Klinik, 2014)
Background: Stroke is the third most common cause of death in the world, with a high prevalence of death in low-and middle-income countries. Hyperglycemia has been associated with atherosclerotic lession resulting in cerebral aneurysm which can lead to hemorrhagic stroke. CT-Scan is considered sufficiently sensitive for detecting acute hemorrhage, as well as detecting mass lessions. The aim of this study was to determine the correlation between hyperglycemia and hemorrhagic stroke incident on noncontrast multislice CT-Scan of the head examination. Methods: This study was an observational study with the analytical approach to the subject of cross-sectional study. 70 subjects were selected by fixed- disease sampling methods. These subjects have been performed a noncontrast multislice CT-Scan of the head examination. Data was collected by reading the result of blood glucose level and CT-Scan of the head examination on patients medical record. Data were processed with Statistical Product and Service Solution (SPSS) 17.00 for Windows Results: Chi-Square models showed that X2 = 7,19 with 5% significancy. OR (Odds Ratio) in hemorrhagic stroke was 4,26 (CI 95% = 1,43-12,74). Patient with hyperglycemia increases the risk of getting hemorrhagic stroke 4,26 (4) times than patient without hyperglycemia. Conclusion: There is a correlation between hyperglycemia and hemorrhagic stroke incident. Keywords: hyperglycemia, hemorrhagic stroke, noncontrast head CT-Scan